How smallholder farmers adapt to climate change: Stories from India—Susila Devi - Devi, S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Susila Devi is a farmer from Jamnapur in India who talks about the importance of education when adapting to changes in the climate. Due to her education she was able to read up on alternative fodder solutions to feed her animals, since the lack of water reduced the regular fodder options. She was able to get a hold of the information at the local milk centre where she also learned about different types of weeds and the importance to keep the animal area clean. Thanks to the new fodder option that Sisula has been giving to her cows, the milk production has increased as well as the fat content. She is now adamant to give her children a proper and lengthy education.